Penggunaan media 3D untuk meningkatkan kemampuan numerasi siswa kelas VI pada mata pelajaran matematika materi bangun ruang di sekolah dasar - Safitri, Rachmawati Adji; Mahfud, Hasan; Supianto, Supianto (Universitas Sebelas Maret, 2023)
This thesis research was carried out based on the existing problems in the field, namely the low numeracy skills of the sixth grade students of SD Negeri 1 Keputran. In this study, three-dimensional media were used in the subject matter of mathematics in geometric shapes. This study used the Classroom Action Research (CAR) method with a descriptive qualitative approach. Data collection techniques used in this study are: observation, interviews, documentation and tests. The results of this study indicate a fairly good increase in each cycle. In cycle I, the percentage of student completeness was 54.54% of a total of 22 students. In the implementation of cycle II, the percentage of student completeness was 68.18% of a total of 21 students. Cycle III obtained the results of the percentage of student completeness of 90.90% of a total of 22 students